Black and blur - Moten, Fred 1962- (Consent not to be a single being, 2017)
"Taken as a trilogy, consent not to be a single being is a monumental accomplishment: a brilliant theoretical intervention that might be best described as a powerful case for blackness as a category of analysis."-Brent Hayes Edwards, author of Epistrophies: Jazz and the Literary ImaginationIn Black and Blur-the first volume in his sublime and compelling trilogy consent not to be a single being-Fred Moten engages in a capacious consideration of the place and force of blackness in African diaspora arts, politics, and life. In these interrelated essays, Moten attends to entanglement, the blurring of borders, and other practices that trouble notions of self-determination and sovereignty within political and aesthetic realms. Black and Blur is marked by unlikely juxtapositions: Althusser informs analyses of rappers Pras and Ol' Dirty Bastard; Shakespeare encounters Stokely Carmichael; thinkers like Kant, Adorno, and José Esteban Muñoz and artists and musicians including Thornton Dial and Cecil Taylor play off each other. Moten holds that blackness encompasses a range of social, aesthetic, and theoretical insurgencies that respond to a shared modernity founded upon the sociological catastrophe of the transatlantic slave trade and settler colonialism. In so doing, he unsettles normative ways of reading, hearing, and seeing, thereby reordering the senses to create new means of knowing